Depurasi timbal (Pb) dari ikan nila nirwana(Oreochromis niloticus) menggunakan pakan yang disubstitusi bungkil kelapa dan kelapa sawit - farida farida; Kukuh Nirmala; Daniel Djokosetiyanto; Hastiadi Hasan (Jurnal Ruaya : Jurnal Penelitian dan Kajian Ilmu Perikanan dan Kelautan, 2020)
Nila fish called Nirwana, which is widely consumed in Indonesia, is an important aquaculture species. Nirwana is extensively cultivated in ponds with different water characteristics that can certainly make the fish contaminated by various toxic and hazardous substances, including lead (Pb). This study analyzed the potential of coconut cake and palm kernel cake to depurate Pb from nirwana. The treatments in this study consisted of 100% commercial feed (Pk), 30% coconut cake + 70% commercial feed (PBK) and 30% palm kernel cake + 70% commercial feed (PBS). Each nirwana used was 100±15 g in weight and injected with 1 mg L-1 of Pb(NO3)2 intraperitoneally. Each test animal was fed at satiation twice a day for eight days. The result of AAS analysis on flesh and feces proved that most Pb was excreted through feces. The highest concentration of Pb which was excreted through feces was PBS treatment (1,46 mg kg-1) on days two, four, six and eight when the Pb concentration was less than 0,001 mg kg-1. The highest fat content in feed was on PBK treatment (13,33%) and PBS (4,78%) with crude fiber content in PBK 0,38% and PBS 7,23%. The results indicated that the coconut cake and palm kernel cake that were added to the feed used could serve as a depuration agent and can reduce Pb from fish through the feces.